The Prospect of Legal Education: an India Overview - Ramaswamy, Hari Hara Sudhan (Journal of Legal Studies, 2020)
Education in India is losing its relevance. This seems much more applicable to the situation in the present day of legal education. This essay aims to focus on two aspects of legal education. Whilst, on one hand, it aims to provide details of the existing legal education system on the other, it aims to drive more attention to the various improvements and developments that are needed. The essay firstly shall describe the existing legal educationsystem. It shall analyze and assess the curricula that are available for the various undergraduate law degrees available in India. It aims to provide an understanding of the perceived distinctions between the three-year law degree and the five-year law degree. As a second aspect, the essay aims to explore options to further the quality of legal education in India by considering examples of various law schools or colleges of law across the world that have consistently proven themselves as a cut-above not legal education and research in their global scale. Also, from the learnings of the gaps in the curricula of the law degrees as discussed previously, the essay shall provide suggestions on the various plausible collaborations with foreign law schools and universities for the benefit of the Indian law schools and colleges of law. As a third and final aspect, as a measure to curb fake or bogus law schools or colleges of law within India and to enhance the employability of law graduates in India at par with those across the globe, the essay aims to provide suggestions applicable for the present-day legal education scenario.